Double whammy: Adverse childhood events and pain reflect symptomology and quality of life in women in substance abuse treatment. (16th March 2017) - Zlotnick, Cheryl; Lawental, Maayan; Pud, Dorit
ABSTRACT: Background. This study examined the profiles of symptoms and health-related quality of life (QOL) of women in substance abuse treatment, comparing those with higher versus lower histories of adverse childhood events (ACE), and those with versus without current pain. Methods. Adult women in outpatient substance abuse treatment ( n = 30) completed questionnaires (cross-sectional study) on topics including drug use, adverse childhood events (ACE), QOL, functional ability, current pain, and depression. Results. Women with pain indicated significant differences in emotional ( p < 0.05), and functional ability ( p < 0.01); but no significant differences were found between women with high versus low levels of ACE. Yet, radar plots of women with both current pain and high levels of ACE, versus those without, portrayed a distinctive profile indicating high levels of anxiety and depression. Conclusions. Rather than a checklist, visual composites of symptoms experienced by women in substance abuse treatment illustrates areas of concern in the overall status of women in substance abuse treatment.